Effect of the Secondary Symbiont Hamiltonella defensa on Fitness and Relative Abundance of Buchnera aphidicola of Wheat Aphid, Sitobion miscanthi - Qian, Li; Jia, Fan; Jingxuan, Sun; Manqun, Wang; Julian, Chen (Frontiers in Microbiology, 2018)
Bacterial symbionts are associated with insects are often involved in host development and ecological fitness. In aphids, the role of these symbionts is variable and not fully understood across different host species. Here, we investigated the symbiont diversity of the grain aphid, Sitobion miscanthi (Takahashi), from 17 different geographical areas. Of these, two strains with the same symbiont profile, except for the presence of Hamiltonella defensa, were selected using PCR. The Hamitonella-infected strain, YX, was collected from a Yuxi wheat field in Yunnan Province, China and the Hamiltonella-free strain, DZ, was collected from a Dezhou wheat field in Shandong Province, China. Using artificial infection with H. defensa and antibiotic treatment, a Hamitonella-re-infected strain (DZ-H) and Hamiltonella-significantly decreased strain (DZ-HT) were established and compared to the Hamiltonella-free DZ strain in terms of ecological fitness. The results indicated that infection with H. defensa (DZ-H strain) increased the fitness of S. miscanthi, which led to increases in adult weight, percent of wingless individuals, and number of offspring. Meanwhile, decreased abundance of H. defensa (DZ-HT strain) resulted in a lower adult weight and wingless aphid rate compared to the DZ-H strain. However, the indices of longevity in both the DZ-H and DZ-HT strains decreased slightly, but were not significantly different, compared to the DZ strain. Furthermore, quantitative PCR showed that the relative abundance of the primary symbiont Buchnera aphidicola in the DZ-H strain was significantly higher than in the DZ strain in all but the first developmental stage. These results indicate that H. defensa may indirectly improve the fitness of S. miscanthi by stimulating the proliferation of B. aphidicola.